Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Pembelian Pada Toko Online Frozenshop Jakarta Barat - Laduni, Mustofa; Nofiana, Lina; Akbar, Mada Faisal (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to examine the influence of product quality and price on purchasing decisions at the West Jakarta Frozenshop online store. This research method uses an associative method with a quantitative approach, namely using in-depth data in the form of numbers with a total of 100 respondents who are consumers at the Frozenshop Online shop in West Jakarta. The sampling method used in this research is to take the entire population to be used as a sample. Based on the research conducted, there is a significant influence, both partially and simultaneously, between price and product quality on purchasing decisions for the West Jakarta Frozenshop Online Store.